The establishment of filiation in transnational situations: practical issues - Sánchez Cano, Mª Jesús (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
The problems of establishing filiation in practice are increased in cross-border situations, due to the different international elements of such situations. The problem can be even more difficult when the filiation is established by a foreign authority and it has not been entered in the Spanish Civil Register. Furthermore, if there is a contradiction between the filiation established by foreign registration and that recorded in the Spanish Civil Register. In those cases, it is necessary to ask what law will be applicable to the establishment of the filiation and whether it is possible to give any effect to the foreign registration documentation.